2009
DOI: 10.1093/cvr/cvp073
|View full text |Cite
|
Sign up to set email alerts
|

Brain nuclear factor-kappa B activation contributes to neurohumoral excitation in angiotensin II-induced hypertension

Abstract: These findings suggest that an ANG II-induced increase in the brain renin-angiotensin system activates NF-kappaB in the PVN and contributes to sympathoexcitation in hypertension. The increased superoxide in the PVN contributes to NF-kappaB activation and neurohumoral excitation in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
197
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(207 citation statements)
references
References 35 publications
7
197
0
3
Order By: Relevance
“…Ang II infusion results in a significant upregulation of NF-kB, RAS, proinflammatory cytokines and oxidative stress, and the interplay between RAS, proinflammatory cytokines and NF-kB leads to a sustained increase in oxidative stress, which contributes to the pathogenesis of hypertension. 2 It was found in this study that the most effective inhibitor of Figure 4 Electrophoretic mobility shift assay (EMSA) for the nuclear transcription factor (NF)-kB in kidney of rats at 25 weeks of age. Nuclear protein was extracted from the kidneys of 25-week-old rats.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Ang II infusion results in a significant upregulation of NF-kB, RAS, proinflammatory cytokines and oxidative stress, and the interplay between RAS, proinflammatory cytokines and NF-kB leads to a sustained increase in oxidative stress, which contributes to the pathogenesis of hypertension. 2 It was found in this study that the most effective inhibitor of Figure 4 Electrophoretic mobility shift assay (EMSA) for the nuclear transcription factor (NF)-kB in kidney of rats at 25 weeks of age. Nuclear protein was extracted from the kidneys of 25-week-old rats.…”
Section: Discussionmentioning
confidence: 86%
“…1 A growing body of evidence indicates that hypertension is an inflammatory state wherein proinflammatory cytokines, such as tumor necrosis factor-a and interleukin-6, contribute to the hypertensive effect. [2][3][4][5] Angiotensin II (Ang II), the major biologically active component of the reninangiotensin system (RAS), not only induces vasoconstriction, aldosterone release and sodium reabsorption by the nephron, but is also intricately interrelated with inflammation. Furthermore, the association of Ang II and inflammation induces an amplification process that involves oxidative stress and proinflammatory transcription factors, leading to progressive vascular injury 6 and having an important role in the development of hypertension and target organ damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also suggest that proinflammatory cytokines and the renin-angiotensin system (RAS) can contribute to these changes (Kang et al 2008a(Kang et al , 2008b(Kang et al , 2009a(Kang et al , 2009b. Our laboratory and others have reported that cytokine blockade in the brain decreases components of the RAS (Kang et al 2008b, Guggilam et al 2008 and that RAS blockade attenuates production of proinflammatory cytokines (Kang et al 2008a(Kang et al , 2009b.…”
mentioning
confidence: 99%
“…Recent studies also suggest that proinflammatory cytokines and the renin-angiotensin system (RAS) can contribute to these changes (Kang et al 2008a(Kang et al , 2008b(Kang et al , 2009a(Kang et al , 2009b. Our laboratory and others have reported that cytokine blockade in the brain decreases components of the RAS (Kang et al 2008b, Guggilam et al 2008 and that RAS blockade attenuates production of proinflammatory cytokines (Kang et al 2008a(Kang et al , 2009b. We inhibited cytokine synthesis in the brain with centrally infused pentoxifylline (PTX) and found that lowering hypothalamic levels of TNF-α and IL-1β without changing plasma cytokine levels is associated with reductions in brain renin, ACE, and AT1-R, strongly suggests that proinflammatory cytokines are intrinsically involved in regulating brain RAS, and thus sympathetic nerve activity and extracellular fluid volume, in rats with HF.…”
mentioning
confidence: 99%